Pengembangan Olahan Belimbing Wuluh Sebagai Upaya Meningktakan Ekonomi Masyarakat Di Pulo Aceh - Saifuddin, Saifuddin; Khumaira, Khumaira; Nazlia, Suraiya; Hasanah, Hasanah; Lestari, Lestari; Taqiyah , Anisah (Pencerah, 2024)
This community service program aims to enhance the economic potential of Pulo Aceh residents by developing processed starfruit (belimbing wuluh) products. Gampong Paloh, Pulo Breuh Subdistrict, is rich in natural resources, including an abundance of starfruit. However, the community's use of starfruit has been limited to producing sunti acid for personal kitchen use, without leveraging its market potential. To address this, the program targeted housewives in fishermen groups, providing training on processing starfruit into dodol, syrup, sunti acid, and jam. The program employed methods such as interviews, outreach, training sessions, discussions, and hands-on mentoring to ensure practical skill development. The outcomes include: (a) increased understanding of entrepreneurship and its role in improving family economies, (b) improved ability to process natural resources into high-quality, marketable products, (c) enhanced skills in producing starfruit-based products such as dodol, jam, and syrup, and (d) better knowledge of packaging, labeling, and simple financial management to create a product identity. The program succeeded in empowering participants with entrepreneurial and processing skills, contributing to economic improvement. Future initiatives should focus on online sales training, establishing a robust e-commerce community, and expanding product diversification to include marine resources, such as tuna and other seafood, to further boost the local economy.